Hosea-Micah - Limburg, James 1935- (Atlanta, GA John Knox, 1988)
Includes bibliographical references.
Keywords: Bible. O.T. Hosea -- commentaries; Bible. O.T. Joel -- commentaries; Bible. O.T. Amos -- commentaries; Bible. O.T. Obadiah -- commentaries; Bible. O.T. Jonah -- commentaries; Bible. O.T. Micah -- commentaries